Analysis of Vo2 Max Levels in Narcotics Correctional Families at Class II B Argamakmur Prison North Bengkulu - Defliyanto; Bayu Insanistyo; Nanda Saputra (UNIB Press, 2022)
This study aims to determine the Vo2 Max level of Narcotics Correctional Families at Class II B Argamakmur, North Bengkulu. This study uses a qualitative research method, with a survey design that aims to find out the general description of the characteristics of respondents which totaled 40 men and measure ments using the Multi level Test Fitness test ( MFT ). The results showed that the age of the respondents was from 18 to 33 years with the youngest being 18 years and the oldest being 33 years. Work respondent previously most are farmers or gardeners with percentage which is very high, and only a few of the in mates are self employed. Based on the results of the tests conducted, it can be stated that out of 40 respondents, it is known that 4 in mates or 10% have a category currently. As well as 36 inmates or 90% have VO2 max test results categorized Less, based on these criteria, Class II B Argamakmur Correctional Families have a level Vo2 max have category Not enough.